MORAL BASES FOR TAKING DECISIONS BY THE FUTURE LEADERS IN BUSINESS - Oleksandr Romanovskiy; Anastasiya Knysh (Університети і лідерство, 2016)
The paper presents analysis of moral basics of decision-making of leaders in business. Relationship between the concepts of "morality" and "moral consciousness" is clarified. Ways of impact of moral leadership on the efficiency of the organization are studied. Basic human values that form the basis of moral profile of the personality of the leader in the business sphere are shown. The author presents a model of moral leadership analysis, that combines classical approach to assessing the moral judgments of L. Kohlberg and approach of determining the moral orientation of the individual of J. Haidt. Relevance and criticism of L. Kohlberg`s research are analyzed. J. Haidt`s concept of "moral principles" and the content of moral principles of modern man are considered in details. On the basis of these two theoretical concepts six options of morality in decision-making are formulated: pre-conventional conservative, conservative conventional, postconventional conservative, pre-conventional liberal, conventional liberal, post-conventional liberal. The results of empirical research of features manifestation of morality in decision making of potential leaders in the business are shown. Recommendation on improving morality of potential and actual leaders are given.